The Suitability of Stool Antigen Testing in the Detection of Helicobacter pylori in a Regional and Rural Area of Australia - Timothy Wearne; Safaa Nadeem; Bruce Wilson; Kylie J. Mansfield; Caitlin Keighley (GastroHep)
Background. Helicobacter pylori is considered the most widespread bacterial pathogen worldwide. Successful eradication protocols are well established, highlighting the importance of appropriate infection detection. Noninvasive testing (NIT) methods are commonly used to detect infection, with test selection dependent on access and previous infection. This study examined trends in NIT by age group and test selection for eradication screening as well as examining H. pylori area prevalence by socioeconomic status (SES) in the Illawarra Shoalhaven and surrounding region. Materials and Methods. This retrospective cohort quantitative study is based on 20,998 NIT including stool antigen test (SAT), urea breath test (UBT), or H. pylori serology via Southern.IML Pathology between 2018 and 2020. Test percentage positives per and total test percentages within age groups were calculated for each NIT. Positive sample postcode data was assigned to socioeconomic percentiles. Total test utilisation and prevalence were calculated and depicted as geospatial representations. Results. Overall: 58.5% UBT, 31% serology, and 10.5% SAT were performed, with 14.7% positive for any NIT. Highest percent positive age group: SAT 80-89yo (18.6%), UBT 0-9yo (20.8%), and serology 90–99yo (32.6%). Test majority per age group: SAT 0-9yo (67.4%), UBT 10-89yo (59.4%), and serology 90-99yo (48.3%). A trend was seen between increasing infection prevalence and increasing socioeconomic disadvantage (p=0.161, R2=0.0361). Prevalence rates visually correlated with total test utilisation. Conclusions. SAT was underutilised compared to UBT or serology. Serology was inappropriately used in older age groups, and the result validity was questioned following confirmed infection. SAT is a viable alternative for use in these settings. No significant correlation was seen between lower SES areas and higher H. pylori infection prevalence, but low-test utilisation suggests likely prevalence underestimation within the studied area and may indicate reduced accessibility to healthcare.